ANTIMICROBIAL TEST OF âTUTUPâ FLOWERS (Macaranga tanarius (L.) Mull.Arg.) - Diana Puspitasari, Fungki Sri Rejeki, Endang Retno Wedowati & (Proceeding of International Congress, 2014)
Preservation âsiwalanâ sap in Lamongan done in two ways, namely by the addition of lime solutionand by addition of liquid of âtutupâ flowers. âTutupâ flowers ((Macaranga tanarius (L.) Mull.Arg.) (nameof Lamongan district) is included in the family Euphorbiaceae. Sugar is produced from the sap with liquidof âtutupâ flowers preservative have better quality than the other sap preservative. The results also showedthat the sap with liquid of âtutupâ flowers preservative have a longer shelf life, with a fewer the number oftotal microbes. Therefore, it needs to be studied a potential âtutupâ flowers extract as an antiâmicrobialmaterial. The purpose of this study is as follows: (1) to know and effectiveness test of âtutupâ flowers preservativeagainst pathogenic microorganisms and food destroyer, (2) to determine part of âtutupâ plantswhich potentially as a preservative, and (3) to determine the minimum concentration of preservative withContact Method.The results showed the following: (1) Growth of Saccharomyces cerevisiae and Staphylococcus aureuscan be inhibited by liquid of âtutupâ flowers, but the growth of Pseudomonas fluorecens are not inhibitedby liquid of âtutupâ flowers; (2) Pseudomonas fluorecens bacterial growth can be inhibited by a solution oflime, but the growth of Staphylococcus aureus and the Saccharomyces cereviseae not inhibited by a solutionof lime; (3) Inhibited the growth of Staphylococcus aureus by addition of âtutupâ plant leaves extractwith concentration 30 % and âtutupâ plant flowers extract with 20% and 30% concentration, inhibited thegrowth of Pseudomonas fluorecens by addition of âtutupâ plant leaves and flowers with 20% and 30% concentration,whereas inhibited the growth of Saccharomyces cereviceae by the addition of leaf extract ofâtutupâ plant with a concentration of 20% and 30% and a flower extract of âtutupâ plant with a minimumconcentration of 10%; and (4) furthermore used flower extract of âtutupâ plant with concentration of atleast 20% can inhibited the growth of Staphylococcus aureus, Pseudomonas fluorecens, and Saccharomycescereviceae.Key words: âtutupâ flowers (Macaranga tanarius); antimicrobial; natural preservatives